SAFETY AND EFFECTIVENESS OF RIBOON-LIKE WIND TURBINE - FLIZIKOWSKI, Josef; Fahad, Raid; ZUBIEDY, Ali (University of Thi-Qar Journal, 2020)
Designing an innovative, ribbon-like wind turbine, a devices to convert wind energy into electricity, requires analysis, simulations and calculations of strength and usefulness characteristics. Such analysis may be carried out on the basis of existing numerical methods. Developed models of the pressure, forces, power and torqu, when converting wind energy with variable speed, for the fundamental innovation. A conceptual design was realized and fundamental numerical strength tests and power of a wind power plant with a turbine which has ribbon blades. Wind turbine with ribbon blades was subjected to safety analysis: strength and efficiency. The obtained results allow to determine the theoretical strength of individual arms of rotor with their maximum displacement. All the results allowed to determine the distribution of the safety factor on the rotor structure, which in theory allows predicting durability during use. The theoretical analysis determined the powers depending from the wind speed, efficiency of the working rotor. Also carried out the elementary analysis of the effectiveness of the existing, new idea, construction of wind power plant with a turbine which has ribbon blades